2013
DOI: 10.1097/qad.0b013e32835f1db0
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events associated with nevirapine and efavirenz-based first-line antiretroviral therapy

Abstract: Compared to NVP, EFV is associated with a lower frequency of severe adverse events, in particular treatment discontinuations. This finding supports a move toward EFV-based therapy as the preferred first-line treatment regimen for HIV treatment within a public health approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
102
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(116 citation statements)
references
References 40 publications
11
102
2
1
Order By: Relevance
“…In the ARROW trial, a nonrandomized comparison of NNRTI‐ based regimens showed favourable short‐term VL suppression with EFV; however, long‐term suppression depended on age, and was better with EFV in children aged < 10 years, and with NVP in those aged > 10 years 79. A recent systematic review and meta‐analysis which included data on nearly 4000 children showed a lower frequency of severe adverse events and treatment discontinuations with EFV than NVP, although EFV use was associated with higher rates of CNS adverse events 80. Overall, these data support the use of EFV as the preferred NNRTI in children aged > 3 years.…”
Section: Which Art Regimen To Start As First‐line Therapymentioning
confidence: 87%
“…In the ARROW trial, a nonrandomized comparison of NNRTI‐ based regimens showed favourable short‐term VL suppression with EFV; however, long‐term suppression depended on age, and was better with EFV in children aged < 10 years, and with NVP in those aged > 10 years 79. A recent systematic review and meta‐analysis which included data on nearly 4000 children showed a lower frequency of severe adverse events and treatment discontinuations with EFV than NVP, although EFV use was associated with higher rates of CNS adverse events 80. Overall, these data support the use of EFV as the preferred NNRTI in children aged > 3 years.…”
Section: Which Art Regimen To Start As First‐line Therapymentioning
confidence: 87%
“…Since NVP and EFV are the only two choices for NNRTIs, it is not surprising that all the cases with TDR were found to contain resistance to NNRTIs. Due to severe adverse effects (hepatotoxicity and allergic reaction), NVP is no longer recommended as a first-line ART drug [45]. Despite neuropsychiatric side effects [46], ART regimens containing EFV demonstrated sustained antiretroviral activity with continued immunologic recovery in the treatment of naïve HIV patients [478].…”
Section: Discussionmentioning
confidence: 99%
“…These reactions mostly occur during the first 18 weeks of treatment [55]. Nevertheless, only a minority of patients develop potentially life-threatening conditions, such as SJS or TEN [57,58]. As occurs with abacavir, rechallenge with nevirapine is associated with allergy reactions characterized by greater severity and a decreased lag period [57,59].…”
Section: Nevirapinementioning
confidence: 99%